Using the Strava application for walking physical activities to control the risk of pre-eclampsia - Suryani Manurung; Tri Riana Lestari; Oktaviyana Tri Handayani (Physical Therapy Journal of Indonesia, 2025)
Background: Pre-eclampsia affects approximately 2–10% of pregnancies worldwide and remains a leading cause of maternal morbidity and mortality. Its occurrence is strongly associated with pregnancy-related risk factors, including elevated blood pressure and excessive maternal weight. This study aimed to evaluate the effectiveness of walking activity, monitored using the Strava application, in controlling blood pressure and reducing the risk of pre-eclampsia among women in their second and third trimesters of pregnancy. Methods: This study employed a quasi-experimental design with a pretest–posttest control group. Thirty pregnant women in their second and third trimesters who were at risk of pre-eclampsia due to elevated blood pressure were purposively recruited, with 15 participants assigned to the intervention group and 15 to the control group. Data collection, conducted between April and May 2024 in Jagakarsa District, South Jakarta, utilized a demographic questionnaire, a blood pressure monitoring sheet, and the Strava application to track physical activity. Blood pressure outcomes were analyzed using paired and independent t-tests. Results: The data followed a normal distribution (p > 0.05). The participants had a mean age of 30.6 years (SD = 5.87), with 46.7% primiparous, 53.3% multiparous, 90% overweight, and 10% normal body weight. Before the intervention, 80% of participants exhibited insufficient physical activity. After the walking intervention monitored via Strava, significant reductions were observed in the intervention group’s systolic blood pressure (from 143.3 to 130.9 mmHg) and diastolic blood pressure (from 92.9 to 86.7 mmHg) (p < 0.05), with mean decreases of 12.4 mmHg and 6.1 mmHg, respectively. By contrast, no significant changes were observed in the control group. Subgroup analysis confirmed significant reductions in blood pressure across confounding factors, including age, parity, and body weight status. Conclusion: Regular walking activity, monitored using the Strava application, was effective in reducing blood pressure and mitigating the risk of pre-eclampsia among women in their second and third trimesters of pregnancy. Incorporating structured physical activity programs during pregnancy, in conjunction with the management of maternal age, parity, and weight, may contribute to the prevention of pre-eclampsia.